2007
DOI: 10.1016/j.jmb.2007.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin Box Structure of the P-TEFb Subunit Cyclin T1 Derived from a Fusion Complex with EIAV Tat

Abstract: SummaryThe positive transcription elongation factor b (P-TEFb) is an essential regulator of viral gene expression during the life cycle of HIV-1. Its Cyclin T1 subunit forms a ternary complex with the viral Tat protein and the TAR RNA element thereby activating cyclin dependent kinase 9 (Cdk9), which stimulates transcription at the level of chain elongation. We report the structure of the cyclin box domain of human Cyclin T1 at a resolution of 2.67 Å. The structure was obtained by crystallographic analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…In the absence of TAR RNA, cyclin T1 formed crystals with an electron density observed for residues 8-263, but no electron density was observed for EIAV Tat. This clearly indicated that cyclin T1 alone could not induce a stable conformation in Tat [288]. In the tripartite TAR RNA-cyclin T1-EIAV Tat complex (see Fig.…”
Section: Tatmentioning
confidence: 89%
See 1 more Smart Citation
“…In the absence of TAR RNA, cyclin T1 formed crystals with an electron density observed for residues 8-263, but no electron density was observed for EIAV Tat. This clearly indicated that cyclin T1 alone could not induce a stable conformation in Tat [288]. In the tripartite TAR RNA-cyclin T1-EIAV Tat complex (see Fig.…”
Section: Tatmentioning
confidence: 89%
“…There are, however, known crystal structures of several complexes that contain Tat fragments. For example, an X-ray structure of the EIAV Tat in complex with cyclin T1 and TAR was reported [288]. Here, a 57-residue segment of EIAV Tat (residues 22-78) was fused via a flexible linker to the cyclin box domain of human cyclin T1.…”
Section: Tatmentioning
confidence: 99%
“…In a previous study, we conducted in silico screening of compounds targeting a site containing the TRM of human CycT1 fused with EIAV Tat (PDB ID: 2PK2) (34). Using this system, we identified three compounds that inhibited HIV-1 replication in acutely infected cells at submicromolar concentrations (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably because the precise mechanism by which these cyclins activate the kinase activity of their corresponding Cdks is not fully understood. In order to clarify the structurefunction relationship of CycT, which is critical for development of effective dominant negative CycT1 mutants, we have previously determined the crystal structure of the cyclin box region of CycT1 (Anand et al, 2007). The resultant three-dimensional structure indicated that CycT1 shares structural similarities with other cyclins (Anand et al, 2007).…”
mentioning
confidence: 99%
“…In order to clarify the structurefunction relationship of CycT, which is critical for development of effective dominant negative CycT1 mutants, we have previously determined the crystal structure of the cyclin box region of CycT1 (Anand et al, 2007). The resultant three-dimensional structure indicated that CycT1 shares structural similarities with other cyclins (Anand et al, 2007). These results suggest that certain functional motifs are well-conserved among cyclin molecules, although there is wide sequence diversity among them.…”
mentioning
confidence: 99%